2011
DOI: 10.1538/expanim.60.455
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Bone Marrow-Derived Cells in the Fracture Callus during Plate Fixation in a Green Fluorescent Protein-Chimeric Mouse Model

Abstract: Abstract:To clarify the distribution of bone-marrow-derived cells in fractures treated by plate fixation, fracture models were created using the green fluorescent protein (GFP) chimeric mouse. We observed 2 types of fracture healing processes with different types of callus formation and cellular events by using Mouse Fix™, a device allowing plate fixation on the mouse femur, and differences in the distribution of bone-marrow-derived cells between the 2 types. The GFP chimeric mice were created by bone marrow t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Periosteal progenitors give rise solely to skeletal cells specifically localized within the developing external callus (39,40). Alternatively, reporter-tagged BM/ BMSC transplantations have demonstrated that BMSCs localize to the fracture gap and may contribute to intramedullary or internal callus formation (13,14). Based on these and other findings, we speculate that skeletal progenitors derived from the periosteum and BM/endosteum contribute differently to bone healing.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Periosteal progenitors give rise solely to skeletal cells specifically localized within the developing external callus (39,40). Alternatively, reporter-tagged BM/ BMSC transplantations have demonstrated that BMSCs localize to the fracture gap and may contribute to intramedullary or internal callus formation (13,14). Based on these and other findings, we speculate that skeletal progenitors derived from the periosteum and BM/endosteum contribute differently to bone healing.…”
Section: Discussionmentioning
confidence: 73%
“…Current dogma suggests that various skeletal progenitors are recruited to the fracture site during bone repair, with at least 2 likely participants being BMSCs and PSCs (36,37). Fracture callus development is known to occur at 3 specific loci: the medullary canal, the area between fractured cortices, and the extramedullary space, including the subperiosteal layer and surrounding soft tissues (13,14). However, the precise identity of cells contributing to callus development and their relative contribution are not well defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…recently, we also reported that bone marrow cells differentiate into osteoblastic cells in response to fractures that are rigidly fixed using a mouse plate fixation device [24]. therefore, the reconstitution of mesenchymal cells may be important for not only the acceleration of hsc engraftment, but also several healing processes after Ucb transplantation.…”
Section: Introductionmentioning
confidence: 84%